2019
DOI: 10.1159/000496211
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Pap Smears in HIV-Positive and HIV-Negative Women from a Tertiary Care Center in South India

Abstract: Objectives: The aim of this work was to study the spectrum of epithelial abnormalities on Pap smears of HIV-positive women categorized as per the Bethesda System of Reporting Cervical Cytology, to correlate them with CD4 lymphocyte counts, and to compare them with the spectrum of abnormalities seen in a HIV-negative control group. Study Design and Methodology: The present study was a 6-year retrospective study conducted in the Department of Pathology at Kasturba Medical College, Mangalore, which included 150 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
2
7
2
Order By: Relevance
“…In Nigeria, the prevalence rate of CECA varies from 5%–11.3% in the northern region [ 29 , 30 ], 11.2%–16.5% in the eastern region [ 31 , 32 ] to 13.9%–34.6% in the western region [ 14 , 33 ]. Similar variation was observed in many LMICs with reported rates of 0.2%–12% in India [ 34 , 35 ], 2.5%–5.7% in Saudi Arabia [ 36 ], 3.7% in Ghana [ 37 ], 3.7% in Oman [ 38 ], 3.8% in Jordan [ 39 ], 4.4% in Kuwait [ 40 ], 5.1% in Turkey [ 41 ], 8.7% in Tanzania [ 42 ] and 14.1% in Ethiopia [ 43 ]. Several factors have been shown to account for this variation.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In Nigeria, the prevalence rate of CECA varies from 5%–11.3% in the northern region [ 29 , 30 ], 11.2%–16.5% in the eastern region [ 31 , 32 ] to 13.9%–34.6% in the western region [ 14 , 33 ]. Similar variation was observed in many LMICs with reported rates of 0.2%–12% in India [ 34 , 35 ], 2.5%–5.7% in Saudi Arabia [ 36 ], 3.7% in Ghana [ 37 ], 3.7% in Oman [ 38 ], 3.8% in Jordan [ 39 ], 4.4% in Kuwait [ 40 ], 5.1% in Turkey [ 41 ], 8.7% in Tanzania [ 42 ] and 14.1% in Ethiopia [ 43 ]. Several factors have been shown to account for this variation.…”
Section: Discussionsupporting
confidence: 86%
“…The odds of developing CECA were 26 times higher among HIV-positive women compared to those who are not. Other studies have also reported a higher prevalence among HIV-positive women compared to their counterparts [ 35 , 43 ]. This is not surprising as HIV/AIDS has been a major risk factor for the development of PCL and CCa due to its association with HPV and immunosuppressive state [ 35 , 37 , 42 , 44 ].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations